Pore characterization and controlling factors analysis of organic-rich shale from Upper Paleozoic marine-continental transitional facies in western Ordos Basin of China. (February 2019) - Fu, Juanjuan; Guo, Shaobin; Liao, Guangzhi
Abstract: In China, marine-continental transitional organic-rich shale gas reservoirs are widely distributed. However, studies on pore systems of this kind of gas shales were relatively rare. In this paper, we investigated the problems about characteristics, genesis, structure of pores in upper Paleozoic of western Ordos basin of China. Various types of pores were identified by the images from focus ion beam scanning electron microscopes (FIB-SEM). Meanwhile, in order to have a better understanding of genesis and influencing factors in pore development process and reservoir features, kerogen microscopic examination, content of organic carbon test, X-ray diffraction, nuclear magnetic resonance (NMR), porosity and permeability tests were performed to collect information of organic geochemistry, mineralogy, pore-size distribution, physical properties. Considering the genesis and position of pores, there are six kinds of pore types found in the research area which including organic pores, interparticle pores in minerals, dissolved pores, intercrystal pores in iron-minerals, intrapore in organic-clay complex and micro fractures. The development of organic pores, which are usually in shapes like bubbles or honeycomb, depends on the organic matter maturity, content of illite and illite-smectite(I/S). The growth of interparticle pores, mostly in triangular and irregular shapes, are mainly controlled by buried depth, content of brittle mineral, illite and I/S. Dissolution pores which formed when clay particles dissolved and intercrystal pores exist in iron-minerals grains, have a great relation with the sedimentary environment and the content of clay minerals. The formation of micro fractures is associated with stress and compaction of layers.